A novel Eu3+/Eu2+ co-doped MgSrLa8(SiO4)6O2 single-phase white light phosphor for white LEDs. Issue 3 (5th January 2017) - Gao, Xiaoli; Liu, Haitao; Yang, Xinyu; Tian, Yiguang; Lu, Xue; Han, Liyuan
Abstract : Under ultraviolet light excitation, the phosphor shows simultaneously the blue emission of the Eu 2+ and the green-yellow-red emission of the Eu 3+ . Abstract : A novel MgSrLa8− x (SiO4 )6 O2 : x Eu (MSLSO: x Eu) phosphor was synthesized through a high-temperature solid-state reaction. The crystal structures, luminescent properties, fluorescence decay time, and oxygen vacancies were investigated systemically. XRD analysis shows a typical oxyapatite structure with the space group P 63 / m . Europium can enter crystal matrices simultaneously in the form of Eu 3+ and Eu 2+ and occupy nonequivalent crystallographic positions in a lattice, thus forming various optical centers. Under ultraviolet light excitation, the phosphors simultaneously show the blue-green emission of Eu 2+ and the green-yellow-red emission of Eu 3+ . The optimal doping content of Eu is 7.5 mol% ( x = 0.075). White light can be realized with a CIE coordinate of (0.3664, 0.3260) by adjusting the concentration of Eu. The lifetimes of Eu 3+ and Eu 2+ in this study are considerably longer than those in other references. The results suggest that the MSLSO:Eu 2+ /Eu 3+ (0.075) phosphor is a promising candidate for white LEDs.